Evaluating affordances of streams and rivers pertaining to children functioning in natural environment - Said, Ismail (Universiti Teknologi Malaysia, 2008)
This study evaluates the affordances of natural water bodies pertaining to functioning of children. Ten children, aged 4-12, were observed experiencing three streams and two rivers in tropical environment. A phenomenological approach yielded a dataset of the children’s behavioral responses derived from a behavioral mapping and an open-ended interview. The responses are physical movement and words and phrases of the children suggesting their preferences or dislikes toward the water settings. The data was analyzed in three stages, firstly, positive or negative affordances, secondly, a taxonomy affordance of children’s outdoor environment, and thirdly, level of affordances. The children experienced 78 positive affordances and only five negative ones. From the taxonomy, the water afforded 11 categories of environmental qualities in which the categories graspable/detached objects and water offered the most number of affordances, 16 and 15, respectively. Most of the children’s activities were performatory and exploratory types. The results suggest that children perceived the affordances of streams and rivers through physical, cognitive and social interactions. The children, therefore, perceived the water bodies as playscapes affording varieties of functional meanings.